Two-step 1,2-shifts by β-cleavage of carbenium ions and recombination in Friedel−crafts reactions of 2-tert-butyl-1-tosylaziridines1 - Bellos, Konstantinos; Stamm, Helmut (The journal of organic chemistry, 1998)
AlCl3-induced ring cleavage of two 2-tert-butyl-1-tosylaziridines in benzene (PhH) or anisole (AnH) generates carbenium ions (CIs). Subsequent neopentyl rearrangement forms CIs 3a,b, whose β-cleavage generates +CH2NTsAlCl3- (14) and an alkene. The intermediate 14 can recombine with the alkene at either CC carbon, resulting in a reversal of the cleavage (3a,b) or in a formal 1,2-shift (CIs 12a,b). AnH rapidly removes 14 from these interconverting systems by formation of a methoxybenzylamide species that undergoes fragmentation into TsNHAlCl3- and methoxybenzyl cation, which gives dianisylmethane (main product). PhH reacts slowly with 14, leaving CIs 3a,b and 12a,b more time for other reactions. Unreacted 14 can even be trapped by AnH at the end of a PhH run. Protonation of each alkene forms N-free CIs that react with PhH and AnH. Replacing tosyl in one of the aziridines by benzoyl makes the β-cleavage markedly slower than both the classic phenyl shift and the internal trapping of CIs.
Gesehen am 12.07.2023